Early intervention with electrical stimulation reduces neural damage after stroke in non-human primates - Jasmine Zhou; Karam Khateeb; Azadeh Yazdan-Shahmorad (Nature Communications)
Abstract For patients experiencing ischemic stroke, acute intervention offers the most critical therapeutic opportunity as it can reduce irreversible tissue injury and improve functional outcomes. However, currently available treatments within the acute window are highly limited and have strict patient selection criteria. Although emerging neuromodulation techniques have been proposed as a treatment for chronic stroke, acute stimulation is rarely studied due to concerns about exacerbating ischemia-induced electrical instability. Here, we demonstrate that acute cortical electrical stimulation, administered one hour post-stroke, provides neuroprotection in non-human primate brains. Using advanced electrophysiology and histology tools, we found that applying continuous theta burst electrical stimulation directly adjacent to the ischemic lesion significantly reduced neural activity in the surrounding tissue, as evidenced by lower electrocorticography signal power and c-Fos expression. This reduced depolarization was accompanied by decreases in neuroinflammation and infarct volume in the sensorimotor cortex. These findings suggest that acute electrical stimulation may serve as a safe and effective early intervention, offering a promising therapeutic strategy to improve outcomes in ischemic stroke.